Case Management In Counseling. - See, Assoc. Prof. Dr., Ching Mey (2005)
In Malaysia, counseling is becoming more acceptable by the population. Counseling services are offered in schools, institutions and community. Thus the role of a counselor is more towards providing individual and group counseling. In this service, the process of meeting the clients needs includes assessment, developing an action plan, consulting and liaising with other community service providers, information sharing and client confidentiality, information and referral, and clients progress tracking.